Konsekwencje de iure oraz de facto umieszczenia podmiotu gospodarczego na liście ostrzeżeń publicznych Komisji Nadzoru Finansowego - Stempniak, Dorota (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
In the herein article, author have focused on consequences that may be experienced by any economic entity placed on the public warning list of the Polish Financial Supervision Authority (PFSA). Although the PFSA has an important role in supervising the financial market it cannot be said that existing legal system is flawless. Those remarks specifically relate to public warning list.In order to present above mentioned consequences, in the first place, author characterize the PFSA and its assured by legal regulations. Subsequently it is pointed out that the activity of placing economic entity on the list is a discretion power of PFSA that cannot be challenged in general or administrative court. It is not a legal decision therefore ones right to defend its rights is being taken away. Therefore the contradiction principle and rules of evidence are not applicable. It is the case of the most vertical relation with public authority.After briefing reader with the legal background the author shows the possible side effects of the PFSA activity that has spillover effect. Loss of reputation or negative perception of business partners and consumers are just the most obvious examples.
Keywords: lista ostrzeżeń publicznych; Komisja Nadzoru Finansowego; rekomendacja M; działalność gospodarcza